Critical review on anti-obesity effects of phytochemicals through Wnt/β-catenin signaling pathway. (October 2022) - Luo, Jinhai; Yu, Zhiling; Tovar, Juscelino; Nilsson, Anne; Xu, Baojun
Abstract: Phytochemicals have been used as one of the sources for the development of anti-obesity drugs. Plants are rich in a variety of bioactive compounds including polyphenols, saponins and terpenes. Phytochemicals inhibit adipocyte differentiation by inhibiting the transcription and translation of adipogenesis transcription factors such as C/EBPα and PPARγ. It has been proved that phytochemicals inhibit the genes and proteins associated with adipogenesis and lipid accumulation by activating Wnt/β-catenin signaling pathway. The activation of Wnt/β-catenin signaling pathway by phytochemicals is multi-target regulation, including the regulation of pathway critical factor β-catenin and its target gene, the downregulation of destruction complex, and the up-regulation of Wnt ligands, its cell surface receptor and Wnt antagonist. In this review, the literature on the anti-obesity effect of phytochemicals through Wnt/β-catenin signaling pathway is collected from Google Scholar, Scopus, PubMed, and Web of Science, and summarizes the regulation mechanism of phytochemicals in this pathway. As one of the alternative methods of weight loss drugs, Phytochemicals inhibit adipogenesis through Wnt/β-catenin signaling pathway. More progress in relevant fields may pose phytochemicals as the main source of anti-obesity treatment. Graphical Abstract: ga1 Highlights: Phytochemicals exhibits anti-obesity effect by Wnt/β-catenin signaling pathway. Multiple compound molecules contribute to anti-obesity effect of phytochemicals. Phytochemicals achieve anti-obesity effect by multi-target in signaling pathway. Phytochemicals make natural products alternative traditional weight-loss drugs. Future research may use more data from animal studies and clinical experiments.